Pelatihan dan Fasilitasi Publikasi Hasil PTK pada Jurnal Tera-kreditasi SINTA bagi Guru MGMP IPA Kota Semarang (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
Abstract One of the aspect in the Teacher’s Continuous Professional Development (PKB) is scientific publications. Teachers are required to publish scientific papers to enhance their professional competence development. Meanwhile, teachers are lacking in generating scientific publications of research results or scientific ideas. Most of the teachers who are members of the MGMP IPA Semarang City said that the lack of scientific publications was due to the teacher's lack of understanding about the analysis of the results of Classroom Action Research (CAR). In addition, teachers also do not understand the flow of scientific publications through scientific journals. Thus, training and facilitating the publication of quality CAR results need to be carried out so that teachers can publish through nationally accredited journals (SINTA accredited). The training program is carried out through 2 stages of activities with 30 participants. The first stage is materials presentation and information on publication assistance. While the second stage is online mentoring via Whatsapp. The materials provided are: 1) CAR and the results of the analysis; 2) writing scientific articles; 3) publication strategy in national journals; and 4) the flow of article publication through OJS. After the material was presented, article writing assistance was carried out through communication on Whatsapp. At the beginning of October, there were 5 articles that managed to get facilitation in the form of publication assistance. Assistance is given to motivate teachers to experience writing in national journals. Keywords: training, classroom action research, publication, OJS, SINTA Abstrak Salah satu komponen dalam Pengembangan Keprofesian Berkelanjutan (PKB) guru adalah publikasi ilmiah. Guru wajib melakukan publikasi ilmiah sebagai wujud pengembangan kompetensi professional. Kegiatan yang umumnya masih kurang dilakukan oleh guru adalah ‘melaksanakan publikasi ilmiah hasil penelitian atau gagasan ilmu pada pendidikan formal’. Sebagian besar guru yang tergabung dalam MGMP IPA Kota Semarang menuturkan bahwa kurangnya publikasi ilmiah disebabkan kurangnya pemahaman guru tentang analisis hasil Penelitian Tindakan Kelas (PTK). Selain itu, guru-guru juga kurang memahami alur publikasi ilmiah melalui jurnal ilmiah. Dengan demikian, pelatihan dan fasilitasi publikasi hasil PTK yang berkualitas perlu dilakukan agar guru-guru dapat publikasi melalui jurnal yang terakreditasi nasional (terakreditasi SINTA). Program pelatihan dilaksanakan melalui 2 tahapan kegiatan dengan 30 orang peserta. Tahap pertama adalah paparan materi dan penginformasian bantuan publikasi. Sedangkan tahap kedua adalah pembimbingan secara daring melalui Whatsapp. Materi yang diberikan adalah: 1) PTK dan hasil analisisnya; 2) penulisan artikel ilmiah; 3) strategi publikasi pada jurnal nasional; dan 4) alur publikasi artikel melalui OJS. Setelah materi dipaparkan, pendampingan penulisan artikel dilakukan melalui komunikasi di Whatsapp. Pada awal Oktober telah terdapat 5 artikel yang berhasil mendapatkan fasilitasi berupa bantuan publikasi. Bantuan diberikan agar memotivasi guru-guru untuk berpengalaman menulis di jurnal nasional. Kata Kunci: pelatihan, penelitian Tindakan kelas, publikasi, OJS, SINTA